Archivio storico dell'Università degli Studi di Firenze (1860-1960) - Capetta, Francesca (Fonti storiche e letterarie - Edizioni cartacee e digitali, 2004)
The Inventory Guide to the Historic Archive is an initial instrument offered by Florence University for the consultation and valorisation of its documentary heritage. It concerns in particular the documents relating to the central administration, from the foundation in 1860 of the Regio Istituto di Studi Superiori Pratici e di Perfezionamento up to 1960, and the fonds of the Faculty of Medical Surgery, formerly Cancelleria degli Studi di S. Maria Nuova and of the Faculty of Arts and Philosophy, formerly the Sezione di studi legali, filologici e filosofici. Part of the fonds of other faculties conserved in the Historic Archive of the University are also described.